The linguistic landscape around community clubs in Singapore - Lin, Beatrice Zi Xin (2019)
Existing research on the linguistic landscape of Singapore, be it on the language choices on multilingual shop signs, or on government-regulated multilingual signs, all reveal and discuss the dominance of English in Singapore’s linguistic landscape. However, little research has been conducted comparing government (official) and non-government (non-official) produced signs to examine the extent to which both sides influence the landscape as a whole. It is acknowledged that Singapore’s linguistic landscape provides insight into how multilingualism is conceptualized and handled differently by the government and their people. Thus, in taking and analysing photographic data from the surroundings of five Community Clubs in Singapore, this study seeks to provide more insight into the languages used in the linguistic landscape of Singapore. The results reaffirm previous findings of the dominance of English but provides an in-depth understanding of the extent of its dominance across both official and non-official signs. Furthermore, this study categorized signs based on whether they are monolingual, bilingual or multilingual, in order to determine how multilingualism manifests itself in the linguistic landscape. Although monolingual English signs dominate the landscape in general, significant differences exist in the appearance rate of bilingual and multilingual signs across the different areas surveyed.